THE EFFECT OF PVC-BASED MEMBRANE COMPOSITION AND Zn(II), Cd(II) AND Pb(II) INTERFERING IONS TO Hg(II) ION SELECTIVE ELECTRODE (ISE) PERFORMANCE BY USING DBA218C6 IONOPHORE - Abd. Wahid Wahab (Universitas Gadjah Mada, 2006)
The effect of PVC (Polyvinylchloride)-Based Membrane Composition to Ion Selective Electrode (ISE)-Hg(II) Performance using Ionophore DBA218C6 (N,N'-Dibenzyl-1,4,10,13-tetraoxa-7,16-diazacyclo octadecane), Plasticizer NPOE (Nitrophenyl Octhyl Ether), Anionic Site KTCPB (Potassium Tetrakis (4-chloro phenyl) borate) have been performed. Membrane compositions used were:(a) PVC (30 mg), NPOE (60 mg), DBA218C6(6 mg) and KTCPB (4 mg); (b) PVC(30 mg), NPOE (60 mg), DBA218C6(7 mg) and KTCPB (3 mg); (c) PVC (30 mg), NPOE (59 mg), DBA218C6 (8 mg) and KTCPB( 3 mg). The concentration range of interference ions Zn(II), Cd(II) and Pb(II) were 1.0 x 10-3 - 1.0 x 10-1 M. ISE-Hg(II) performance for membrane composition of 30 : 60 : 6 : 4 was 26.34 mV per decade (Nernstian Slope value) on Hg(II) concentration range of 1.0x10-6 - 1.0 x 10-1 M , membrane composition of 30 : 60 : 7 : 3 was 27.71 mV per decade on Hg(II) concentration range of 1.0 x10-6 - 1.0 x10-1 M, and membrane composition of 30 : 59 : 8 : 3 was 28.52 mV per decade on Hg(II) concentration range of 1.0 x10-6 - 1.0 x10-1 M with activity between pH 1.0-3.0. The concentration of interference ions : Zn(II), Cd(II) and Pb(II) in the range of 1.0 x 10-3 - 1.0 x 10-1 M with the ratio of the primary ion to interference ions of 4 : 1 gave real effect. As results, selectivities and sensitivities between ISE-Hg(II) and Ionophore DBA218C6 could be determined by PVC-Based Membrane Composition and the effect of Zn(II), Cd(II) and Pb(II) interference ions was observed in the concentration of 1,0 x10-3 - 1,0 x10-1 M.